Morphological changes of the human face after massive weight-loss due to bariatric surgery. Issue 7 (July 2020) - Peters, Florian; Kroh, Andreas; Neumann, Ulf P.; Ulmer, Florian T.; Möhlhenrich, Stephan Chr.; Bock, Anna; Hölzle, Frank; Modabber, Ali
Abstract: The aim of this study was to evaluate the morphological changes in the face of obese patients during massive weight loss using a more reliable method than two dimensional photographs or tape measures. The faces of 23 patients were recorded prior to and six months after bariatric surgery. Distances between important anatomical landmarks of the face were calculated and the volume of the neck was compared. The distance between the Tragion and Subnasale (132.7 ± 6.804 mm to 131.5 ± 6.866 mm; p = 0.0003), and the distance between Tragion and Stomion became significantly longer 136.0 ± 8.016 mm to 134.3 ± 7.698 mm; p = 0.0031), while distances between the Tragion and Pogonion (150.2 ± 8.216 mm to 148.3 ± 8.383 mm; p < 0.0001), Tragion and Menton (152.3 ± 9.037 mm to 148.9 ± 9.623 mm; p < 0.0001), and Tragion and tip of the nose (144.9 ± 7.273 mm to 144.0 ± 7.416 mm; p = 0.0023) were significantly reduced. The mean volume loss of the neck was 75.218 ± 40.197 ml. No significant correlation was found between total weight loss and cervical volume loss (r = 0.3447; p = 0.1072). The morphological changes of the face after massive weight loss vary in different areas of the face. Patients and their attending physicians must be aware of the face's morphology change after massive weight loss in an extent that does not correlate with the total weight loss of the patient.